Evaluation of Water Quality Based on Macrozoobenthos as a Bioindicator in Ngesong Spring and the Ditch, Batu-East Java - Susanto, Muhamad Azmi Dwi; Retnaningdyah, Catur; Leksono, Amin Setyo (Universitas Brawijaya, 2024)
Ngesong Spring is a clean spring that is used by society as a spring of clean water and as a tourist attraction. The Ngesong spring has a ditch that flows to the society settlement, where the water is used for agricultural and plantation irrigation. The utilization of the Ngesong Spring as a tourist attraction and its ditch through agriculture, settlements, and society settlements has great potential to cause pollution and degradation of water quality, so it is necessary to evaluate water quality. Therefore, it is necessary to monitor the quality of this water, one of which is the use of the macrozoobenthic community structure as a bioindicator. The research was conducted in four locations, namely, a water spring and the channels that will be used for agriculture, plantations, and settlement activities, in September and October 2022. The variables observed in this study included the physicochemical quality of the water, namely, the water temperature, conductivity, power of hydrogen (pH), dissolved oxygen (DO), biological oxygen demand (BOD), and total suspended solids (TSS), as well as the community structure and macrozoobenthos diversity. The results of this study indicate that 26 macrozoobenthic families belong to 12 orders, for a total of 968 individuals. Water springs had the highest diversity and evenness index values, with H = 2.27 and E = 0.54. The analysis of macrozoobenthic family relationships as an indicator of water quality using the family biotic index (FBI) and average score per taxon (ASPT) showed that the watershed site has very clean water and no organic pollution. At watersheds with good water quality, the families Perlidae, Nemouridae, Limnephilidae, Viviparidae, Chironomidae, and Euphaeidae were found. Moreover, In this study, the locations that have highly organically polluted waters are ditches that have agricultural activities and settlement activities.